Stroke in Women - Oral Contraception, Pregnancy, and Hormone Replacement Therapy - Rantanen, Kirsi; Tatlisumak, Turgut (Current Vascular Pharmacology, 2013)
Stroke is a devastating disease affecting millions of people worldwide every year. Female stroke victims have higher mortality rates and they do not re-cover as well as men. Women's longevity and different vascular risk factor burden like a larger prevalence of atrial fibrillation play a role. Women also have unique risk factors such as oral contraception, pregnancy, estrogen decrease after the menopause and hormone replacement therapy, which should all be evaluated and taken into consideration in treatment decisions both in the acute phase of stroke and in secondary prevention. In this review, the evidence regarding these hormonal aspects and the risk of stroke in women are evaluated. The relevant guidelines are studied and research gaps identified. Future topics for research are recommended and current treatment possibilities and their risks discussed.
Keywords: Hormonal replacement therapy